Development Histories, AMR Futures, and the Biosociality of a ‘Hotspot' - Andrea Butcher (Engaging Science, Technology, and Society)
Paul Rabinow identified ‘practices of life’ as a potent site of twenty-first-century knowledge and power, arguing that instruments of genomic characterisation will reshape contemporary social relations, thus establishing a new politics of the molecular. Rabinow named this new epoch biosociality. In Antimicrobial Resistance (AMR) surveillance terms, gene sequencing technologies and bioinformatics programmes are used to determine resistance profiles of humans, nonhuman animals, and the environments they are embedded within. A regime of global governance has grown around the statistical analysis of the data produced by these new technologies, in which geographic locations displaying certain resistance profiles are designated as ‘hotspots’ of resistance emergence, justifying intervention in the behaviours of the populations inhabiting them.